Associations of depressive symptoms with disability-free life expectancy and self-assessed healthy life expectancy in middle-aged and older adults: Results from a longitudinal population-based study in China. (July 2022) - Huang, Guogui; Guo, Fei; Luo, Yanan
Highlights: Although the health consequences of depression had been extensively examined, most of the existing research focused on the relationships between depression and mortality with less attention to non-fatal conditions. This study aimed to explore the relationships of depressive symptoms with both mortality and morbidity among middle-aged and older adults in China. Depressive symptoms were found to be associated with reductions in total life expectancy (TLE), disability-free life expectancy (DFLE) and self-assessed healthy life expectancy (SHLE). Abstract: Objectives Although the health consequences of depression have been extensively examined, little attention has been given to its nonfatal conditions. This study aims to investigate the association of depressive symptoms with total life expectancy (TLE), disability-free life expectancy (DFLE) and self-assessed healthy life expectancy (SHLE). Methods Data were sourced from the China Health and Retirement Longitudinal Study 2011–2013. The 10-item Center for Epidemiologic Studies Depression Scale (CES-D-10) short form was used to measure depressive symptoms in 14, 982 Chinese middle-aged and older adults. The population-based multistate life table method was used to estimate the differences in TLE, DFLE and SHLE by the status of depressive symptoms. Results At the age of 45 years, depressive symptoms were associated with a reduction of 1.8 (95% CI: 0.4–3.2) additional years of TLE. The estimated depression-induced reduction in TLE was 1.8 (95% CI: 0.1–3.5) in females, and 2.6 (95% CI: 1.0–4.2) in males. For DFLE, a reduction of 3.1 (95% CI: 2.0–4.2) additional years was found in individuals with depressive symptoms. The proportion of DFLE in TLE in participants with depressive symptoms decreased compared with that of the non-depressive symptoms group (depressive symptoms: 87.4% vs non-depressive symptoms: 91.4%). For SHLE, on average, individuals with depressive symptoms suffered a reduction of 7.6 (95% CI: 6.5–8.7) additional years in their SHLE at 45 years old and a reduction in the proportion of SHLE in TLE by 17.7%. Similar patterns were found in groups aged 55, 65, 75 and 85 years. Conclusion This study showed that depressive symptoms were associated with reductions in TLE, DFLE and SHLE among middle-aged and older adults in China, and the depression-induced reduction in proportions of DFLE and SHLE in TLE continued to increase as age increased. This study provides new insight into the nonfatal health consequences of depressive symptoms and their adverse effects on quantity and quality of life. Our findings are useful for policy makers and individuals in mental health management, depression prevention and intervention and informing health policies.